Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/cells12040527
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Aging: An Emerging Hallmark?

Abstract: Extracellular vesicles (EVs) are membrane-enclosed particles secreted by cells and circulating in body fluids. Initially considered as a tool to dispose of unnecessary material, they are now considered an additional method to transmit cell signals. Aging is characterized by a progressive impairment of the physiological functions of tissues and organs. The causes of aging are complex and interconnected, but there is consensus that genomic instability, telomere erosion, epigenetic alteration, and defective prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 167 publications
(235 reference statements)
0
3
0
Order By: Relevance
“…In a study by Khayrullin et al, a lipidomic analysis of serum extracellular vesicles revealed that the serum EVs of older women were highly enriched in ceramide and were significantly different from those of younger women [34]. Very long chain lipotoxic ceramides can cause mitochondrial dysfunction, oxidative stress and cell death in cardiomyocytes [5]. Thus, EV-derived ceramide represents a novel factor in the aging process that may contribute to degeneration in many organs and tissues [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Khayrullin et al, a lipidomic analysis of serum extracellular vesicles revealed that the serum EVs of older women were highly enriched in ceramide and were significantly different from those of younger women [34]. Very long chain lipotoxic ceramides can cause mitochondrial dysfunction, oxidative stress and cell death in cardiomyocytes [5]. Thus, EV-derived ceramide represents a novel factor in the aging process that may contribute to degeneration in many organs and tissues [34].…”
Section: Discussionmentioning
confidence: 99%
“…To combat these effects of aging, researchers are exploring various strategies and trying to develop anti-aging therapies [ 125 , 126 ]. Recent studies suggest that EVs isolated from different types of stem cells may be a promising tool for combating aging-related inflammation and dysfunction of macromolecules [ 126 , 127 , 128 ]. EVs can transport a variety of bioactive molecules, such as microRNAs and proteins, that have the potential to modulate various cellular processes and promote tissue regeneration [ 129 ].…”
Section: Evs As Integrators Of Homeostasismentioning
confidence: 99%
“…Notably, advanced age stands as one of the primary risk factors for AD [41]. Aging is associated with an increase in the BBB as well as intestinal permeability, which, in turn, has been linked to elevated blood levels of host and bacterial vesicles [260][261][262][263]. When orally administered to mice, BEVs from Paenalcaligenes hominis (P. hominis)-bacteria that are found at significantly higher levels in the gut microbiota of elderly individuals-triggered microglia activation, neuroinflammation, and cognitive impairment [239].…”
Section: Bacterial Extracellular Vesicles As Promoter Of Neurodegener...mentioning
confidence: 99%